The undergraduate medical student's perception of professional mentorship: Results from a developing nation's medical school - Adeyi A Adoga; Daniel D Kokong; Nuhu K Dakum; Nuhu D Ma'an; Andrew A Iduh; Emoche T Okwori; John P Yaro (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: There are no documented formal mentoring programs for medical students in Nigeria. This study aims to determine the perception of undergraduate medical students at the University of Jos on professional mentorship, with a view to informing University authorities on creating and developing a mentoring program. MATERIALS AND METHODS: A cross-sectional study conducted in December 2017 in which self-administered questionnaires were distributed among the sixth-year medical students in a University in North-Central Nigeria, eliciting information regarding biodemographic data, knowledge of and experiences with mentoring, desired benefits of mentoring, and the willingness to participate in a mentoring relationship. Data collected was analyzed with EPI Info statistical software® version 7.2.1 (EPI Info, Center for Disease Control, Atlanta, Georgia, 2017). RESULTS: In a class of 166, the response rate was 83.5%. Mean age = 27.4 years; standard deviation = ±2.6 with a male: female ratio of 1.9:1. Moderate knowledge of mentoring was reported by 47 (44.3%). Attitude toward mentoring was very positive in 23.6%. One hundred and four (98.1%) students agreed mentoring are effective in developing potential. Nearly 95.3% agreed a mentorship program would benefit medical students with 70.8% expressing high willingness to participate. A weak positive statistical correlation between the age of students and those who expressed willingness to participate was recorded (r = 0.04; 95% confidence interval (CI) = 0.6-1.16; and P = 0.05). CONCLUSION: Sixth-year medical students of the University of Jos have a moderate knowledge of and a good attitude toward mentorship. The implementation of a formal mentoring program for medical students at the University of Jos is strongly recommended.